2014
DOI: 10.1021/nn406367p
|View full text |Cite
|
Sign up to set email alerts
|

All-Nanosheet Ultrathin Capacitors Assembled Layer-by-Layer via Solution-Based Processes

Abstract: All-nanosheet ultrathin capacitors of Ru0.95O20.2-/Ca2Nb3O10-/Ru0.95O20.2- were successfully assembled through facile room-temperature solution-based processes. As a bottom electrode, conductive Ru0.95O20.2- nanosheets were first assembled on a quartz glass substrate through a sequential adsorption process with polycations. On top of the Ru0.95O20.2- nanosheet film, Ca2Nb3O10- nanosheets were deposited by the Langmuir-Blodgett technique to serve as a dielectric layer. Deposition parameters were optimized for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 45 publications
4
55
0
1
Order By: Relevance
“…Electrochemical capacitors are promising candidates for energy storage devices owing to their high specific power and long cycle life, and efforts are being made to develop in-plane or ultrathin all-solid-state supercapacitors (97), which are intriguing energy storage components for flexible/stretchable and portable electronic devices with high safety requirements. To improve the specific capacitance of carbonaceous electrochemical double-layer capacitors that store energy by means of reversible electroadsorption of ions in the Helmholtz double layer at the electrode/electrolyte interface, graphene-based supercaps have been hybridized with pseudocapacitive nanosheets, including transition metal oxides, hydroxides, and chalcogenides.…”
Section: Capacitorsmentioning
confidence: 99%
“…Electrochemical capacitors are promising candidates for energy storage devices owing to their high specific power and long cycle life, and efforts are being made to develop in-plane or ultrathin all-solid-state supercapacitors (97), which are intriguing energy storage components for flexible/stretchable and portable electronic devices with high safety requirements. To improve the specific capacitance of carbonaceous electrochemical double-layer capacitors that store energy by means of reversible electroadsorption of ions in the Helmholtz double layer at the electrode/electrolyte interface, graphene-based supercaps have been hybridized with pseudocapacitive nanosheets, including transition metal oxides, hydroxides, and chalcogenides.…”
Section: Capacitorsmentioning
confidence: 99%
“…In recent years, RuO 2 NSs exfoliated from bulk rutile RuO 2 have been used in lithium-oxygen and lithium-ion battery applications because exfoliation facilitates the fabrication of NSs 15,16 . Wang et al 17 reported obtaining a sheet resistance of 4.1 kΩ sq −1 from RuO 2 NS films at room temperature, although most of their work focused on all NS ultrathin capacitors. Recently, Lee et al 18 also demonstrated the optimization Samsung-ro, Yeongtong-gu, Suwon-si, Gyeonggi-do 16678, Republic of Korea Full list of author information is available at the end of the article of electrode performance using exfoliated 2D RuO 2 NSs as a conducting additive.…”
Section: Introductionmentioning
confidence: 99%
“…11),15), 16) Because MnO 2 nanosheets are redoxable, they are expected to be suitable for energy storage devices or solar cells, and their electrode properties for use lithium-ion batteries have been examined. 17) Lithium-ion rechargeable batteries have the advantage of higher energy density than other types of commercial batteries, therefore they are used as energy-storage instruments in various mobile electric devices.…”
Section: )3)mentioning
confidence: 99%
“…RuO 2.1 nanosheets (or Ru 0.95 O 2 nanosheets) should also have the Ru-site vacancy of this type. 6), 16) While in the other study the concentration of the vacancy defects is fixed, the process employed here has the potential to control the concentration of the vacancy defects by changing the composition of the starting material or the condition of acid-restacking.…”
Section: )mentioning
confidence: 99%